McMafia : a journey through the global criminal underworld - Glenny, Misha (New York, N.Y. : Vintage Books, 2009)
"With the collapse of the Soviet Union, the fall of the Berlin Wall, and the deregulation of international financial markets in 1989, governments and entrepreneurs alike became intoxicated by dreams of newly opened markets. But no one could have foreseen that the greatest success story to arise from these events would be the world-wide rise of organized crime. Today, it is estimated that illegal trade accounts for one-fifth of the global GDP."--Cover.
Foreword to the Vintage edition -- Introduction -- pt. I. The fall of communism -- Death of an American -- Bloody lucre -- The Mafiya : midwives of capitalism -- Spreading the word -- pt. II. Gold, money, diamonds, and banks -- Aliyah -- Xanadu I -- Xanadu II -- The theater of crime -- Black and white -- pt. III. Drugs and cybercrime -- Buddies -- March of fear -- Code Orange -- pt. IV. The future of organized crime -- The overunderworld -- The future of organized crime -- Epilogue -- Acknowledgments -- A note on sources -- Index.
"With a new foreword."--Cover.
Includes bibliographical references and index.
Keywords: Organized crime; Transnational crime; Organized crime; Transnational crime